Facile Assembly of Thermosensitive Liposomes for Active Targeting Imaging and Synergetic Chemo-/Magnetic Hyperthermia Therapy - Yanli An; Rui Yang; Xihui Wang; Yong Han; Gang Jia; Chunmei Hu; Zhiyuan Zhang; Dongfang Liu; Qiusha Tang (Frontiers in Bioengineering and Biotechnology)
Cancer stem cells (CSCs) are thought to be responsible for the recurrence of liver cancer, highlighting the urgent need for the development of effective treatment regimens. In this study, 17-allylamino-17-demethoxygeldanamycin (17-AAG) and thermosensitive magnetoliposomes (TMs) conjugated to anti-CD90 (CD90@17-AAG/TMs) were developed for temperature-responsive CD90-targeted synergetic chemo-/magnetic hyperthermia therapy and simultaneous imaging in vivo. The targeting ability of CD90@DiR/TMs was studied with near-infrared (NIR) resonance imaging and magnetic resonance imaging (MRI), and the antitumor effect of CD90@17-AAG/TM-mediated magnetic thermotherapy was evaluated in vivo. After treatment, the tumors were analyzed with Western blotting, hematoxylin and eosin staining, and immunohistochemical (IHC) staining. The relative intensity of fluorescence was approximately twofold higher in the targeted group than in the non-targeted group, while the T2 relaxation time was significantly lower in the targeted group than in the non-targeted group. The combined treatment of chemotherapy, thermotherapy, and targeting therapy exhibited the most significant antitumor effect as compared to any of the treatments alone. The anti-CD90 monoclonal antibody (mAb)-targeted delivery system, CD90@17-AAG/TMs, exhibited powerful targeting and antitumor efficacies against CD90+ liver cancer stem cells in vivo.